(untitled) (Global Journal of Human-Social Science, 2012)
In recent years with the innovation and adjustment of financial market hedge funds grown rapidly and became the major actor in the world financial market The main law on investment adviser is the Investment Advisers Act of 1940 and the US amended it in 2004 In 2010 the Private Fund Investment Advisers Registration Act of 2010 made further amendment to the Investment Advisers Act of 1940 The continuously strengthened regulation on investment advisers in the US is of great significance for China